Comparison of isozyme and RAPD patterns for analysis of the genetic relationship in Dendrobium crystallinum and D. sp - S. Inthawong (2018)
The genetic relationship in two Dendrobium species which had similar morphology was analyzed using cluster analysis by UPGMA from their isozyme and RAPD data. It was found that dendrogram of eight isozyme systems could distinguish D. crystallinum from D. sp. However, it could not distinguish a clone of D. sp. On the other hand, dendrogram of RAPD analysis from eight primers could identify D. crystallinum from D. sp. and a clone of D. sp.